(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to indentify: Intuitive thinking among Female students in kindergarten department. Social control among Female students in kindergarten department. Correlational relationship between in Intuitive thinking and Social control among Female students in kindergarten department. To achieve the research objectives, the researcher adopted the intuitive thinking scale of (Al-Safi, 2022), which consists of (40) paragraphs distributed over four fields and five alternatives, and adopted the social control scale of (Al-Shahabi, 2018), which consists of (64 paragraphs) distributed over three fields and five alternatives. After verifying the psychometric properties of the two scales, the researcher applied them to the research sample of (200 female students) from the kindergarten department. After analyzing the data, the researcher reached: Kindergarten students are characterized by intuitive thinking. Kindergarten students are characterized by Social control. There is a direct correlation between intuitive thinking and social control among kindergarten students.